Development of Washed Cell Fowl Cholera Vaccine in Bangladesh - Akand, M.S.I.; Choudhury, K.A.; Kabir, S.M.L.; Sarkar, S.K.; Amin, K.M.R. (International Journal of Poultry Science, 2004)
An experiment was conducted to develop washed cell fowl cholera (WCFC) vaccine with virulent avian Pasteurella multocida (PM 38) serotype 1 (X-73). A total of 20 Fayoumi birds of either sex of 10 weeks aged were divided into two groups as group A (immunized with washed cell fowl cholera vaccine) and group B (unvaccinated control). Primary vaccination was given through IM route in each birds of group A and booster dose was given through SC route after 15 days of primary vaccination. The presence of antibody against P. multocida was determined by slide agglutination test (SAT) and growth inhibition test (GIT). The degree of antibody levels of prevaccination and post vaccination sera were determined by passive haemagglutination assay (PHA). Sera mean PHA titres at 15, 21, 28 and 42 days post-vaccination in group A were 30.4±4.43, 46.4±6.06, 67.2±11.14 and 134.4±22.28 respectively. The present results revealed that WCFC vaccine worked satisfactory in terms of protection rate against Avian Pasteurellosis. It was also demonstrated that experimental WCFC vaccine conferred 80% protection against challenge infection when all chickens of control group failed to survive against challenge infection.